Integrasi Teknologi Pada Tanaman Obat Dan Pengobatan Tradisional Di Tanjung Medan Sumatera Utara Berbasis Android - Samsir, Samsir; Yani, Juli Yani; Azhar Ritonga, Wahyu; Alfauzan Harahap, Ridho; Andriyani, Dewi (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Regional conditions The indigenous people of Tanjung Medan have a long tradition of using local plants as medicine for various diseases, including fever, cough, diarrhea, cancer, and diabetes. The people of Tanjung Medan use a variety of plants—up to 163 species from 56 families—to treat about 23 types of diseases. It is widely used to cure supernatural and natural diseases such as fever, cough, diarrhea, cancer, and diabetes. The dominant plant families include Zingiberaceae (ginger) and Rutaceae. But it is a problem of many neglected and even lost medicinal plants and medicine traditions now among the people of Tanjung Medan, especially in the current generation Z. The method used is participatory-based counseling which includes educational lectures, leaflet distribution, and question and answer sessions. The material presented included drug classification, how to obtain drugs legally, the use of drugs according to the rules, correct storage, and safe disposal of drugs. The results of the activity showed high enthusiasm from the participants and increased their understanding of drug management at home. The question and answer session showed the activeness of the participants and became an indicator of the success of the delivery of the material. The DAGUSIBU program has proven to be relevant in increasing public health literacy and supporting efforts to prevent the abuse of chemical drugs, but it is better to use traditional medicine from processed plants themselves. This kind of education is expected to shape a wiser, more responsible, and rational community behavior in the use of drugs.